Cinephilia Movies, Love and Memory - de Valck, Marijke; Hagener, Malte (Film Culture in Transition, 2005)
This anthology explores new periods, practices and definitions of what it means to love the cinema. The essays demonstrate that beyond individualist immersion in film, typical of the cinephilia as it was popular from the 1950s to the 1970s, a new type of cinephilia has emerged since the 1980s, practiced by a new generation of equally devoted, but quite differently networked cinephilies. They obsess over the nuances of a Douglas Sirk or Ingmar Bergman film; they revel in books such as François Truffaut's Hitchcock; they happily subscribe to the Sundance Channel-they are the rare breed known as cinephiles. Though much has been made of the classic era of cinephilia from the 1950s to the 1970s, Cinephilia documents the latest generation of cinephiles and their use of new technologies. With the advent of home theaters, digital recordings devices, and online film communities, cinephiles today pursue their dedication to film outside of institutional settings. A radical new history of film culture, Cinephilia breaks new ground for students and scholars alike.